2019
DOI: 10.1085/jgp.201812263
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants are modifiers of lipid bilayer properties

Abstract: The two major classes of antidepressants, tricyclic antidepressants (TCAs) and selective serotonin reuptake inhibitors (SSRIs), inhibit neurotransmitter reuptake at synapses. They also have off-target effects on proteins other than neurotransmitter transporters, which may contribute to both desired changes in brain function and the development of side effects. Many proteins modulated by antidepressants are bilayer spanning and coupled to the bilayer through hydrophobic interactions such that the conformational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 87 publications
(167 reference statements)
7
71
0
Order By: Relevance
“…It is increasingly recognized that the biophysical properties of the membrane, whether in physiological or in vitro conditions, influence the structure and function of many membrane‐associated proteins . One reason is that the molecular mechanisms of membrane proteins often entail transient or persistent deformations in the surrounding membrane; thus, alteration of the elastic properties or natural curvature of these membranes, through variations in their lipid composition, is one way to regulate protein activity.…”
Section: Resultsmentioning
confidence: 99%
“…It is increasingly recognized that the biophysical properties of the membrane, whether in physiological or in vitro conditions, influence the structure and function of many membrane‐associated proteins . One reason is that the molecular mechanisms of membrane proteins often entail transient or persistent deformations in the surrounding membrane; thus, alteration of the elastic properties or natural curvature of these membranes, through variations in their lipid composition, is one way to regulate protein activity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, both the vesicular and the plasma membranes (near the release sites) are exposed to a considerable amount of serotonin. Small amphipathic molecules, for example, specific anesthetics, are known to alter the physical properties of the membrane, such as membrane fluidity [26][27][28][29][30] . If serotonin also does so, then that in turn can affect cellular functions, including membrane protein function, membrane affinity of other molecules as a prerequisite for subsequent receptor binding, and key cellular processes such as exocytosis and endocytosis.…”
Section: Mainmentioning
confidence: 99%
“…[20] Small amphipathic molecules, for example,s pecific anesthetics, are knownt oa lter the physical properties of the membrane, such as membrane fluidity. [21][22][23][24][25] It has also been shown that isothermal compressibility of lipid monolayers can be alteredb ys mall serotonin-related molecules (such as melatonin) at % 1mm concentration, and even by serotonin at higher concentrations. [26] Furthermore, serotonin binding to raft-like mixed model membranes was shown to alter domain size.…”
Section: Introductionmentioning
confidence: 99%